Analyzing The Impact of Database Design on The Success of Regional Information Systems - Buulolo, Viktor Dirman Jaya; Azzahra, Syakirah; Sembiring, Dealova Venolika Br; Hasanah, Nur Citra; Irawan, Irawan (EDUCTUM: Journal Research, 2025)
Database design is a fundamental component in the development of Regional Information Systems (RIS), as it determines data quality, inter-agency integration, system performance, and the sustainability of public services. This study aims to analyze the impact of database design on the success of RIS implementation by examining aspects of data quality, system integration, operational efficiency, information security, decision-making support, and system scalability. The research employs a literature review and conceptual analysis of various database design models and their implementation within local government environments. The results indicate that effective database design characterized by standardized data structures, clear inter-table relationships, strong data validation, and multi-layered security mechanisms significantly enhances the effectiveness and accuracy of regional data management. Conversely, suboptimal database design leads to data duplication, low interoperability among local government units, slower public service processes, and an increased risk of data breaches. Therefore, the success of Regional Information Systems is strongly influenced by the quality of database design as the primary foundation for data processing and information provision in local governments.